Powinności w perspektywie pojęć niedookreślonych . Płaszczyzna orzecznictwa sądów administracyjnych - Kręcisz, Wojciech (Kwartalnik Prawa Publicznego, 2016)
Applicable legal norms, subjecting their addressees to defined behavior patterns, should have – and do have – uniform and consistent axiological foundations, and thus, what serves to implement and protect certain values as their function. Taking into account the dynamics of broadly understood phenomena and social, economic or political processes – due to the functions of law as the regulator of these processes – the legislator must not fail to provide, through the use of specific legislative techniques, the lack of dynamics of the legal system itself, and therefore its flexibility. Whereas the legislator accounts for the rules in force in this respect and satisfies the rational model of law-making, vague and blurred pronouncements, estimates and assessments – which he or she makes for that purpose based on legislative provisions or extrinsic references to evaluations expressing certain values, in view of the requirement to preserve the precision of normative expression and to avoid its ambiguity, can in principle not be assessed as an undesirable malfunction or infirmity in the text of a given legal act. The broadly defined vague (blurred) terms used by the legislator not only affect the course of the interpretation of a rule of law, they also influence its outcome and consequently the possibility and even the necessity of assessing the correctness of implementation of the “duties” that are updated in relation to the vague concepts. The act of applying law, expressed in the resolution of a particular content, shaping the rights and/or the duties of the subject to whom it is addressed, should correspond to a certain standard. The duties of administrative courts in the approach to vague terms – or, more broadly, in their perspective – they must not fail to account for the constitutional background and the context it defines. Especially since the primary purpose and task of the administrative judiciary bodies (and the direct reason for their establishment) is to protect the individual’s freedoms and rights.